Living with Little Money: A Study on Rural Poverty - Fernández Carvajal, Doris (2018)
This article is based on a research study entitled “Survival Strategies in Poor Households from a Gender Perspective,” conducted at the Women Studies Institute from the National University of Costa Rica between 2014 and 2015. This study provides an “X-ray” examination on how poverty was faced by a group of rural families residing in the communities of Acosta, Chira Island and Palenque Margarita in the provinces of San José, Puntarenas and Alajuela, respectively. The paper emphasizes the economic dimension of the families particularly in terms of income and expenses, showing how their economic resources are generated, what they are used for, who contributes to them, how they are used to meet the families” vital needs such as food, housing, healthcare, recreation, and clothing, and how all this impacts the families” quality of life. The information was collected through a questionnaire applied to fifty nuclear homes headed by a single mother. One of the most relevant findings of this study is that it validates the methodological effectiveness of a study on poverty from a multidimensional perspective. In the case of the poor rural homes analyzed, although they have low income, they also have several aspects that help them improve their quality of life and generate feelings of social inclusion, such as having access to a basic diet and healthcare and owning their own house.